Selected applications of cash flow models of life insurance. - Hoang, Thu Giang (2020)
The thesis deals with the practical applications of a cash flows model in a life insurance company accompanied by illustrative numerical examples. Specifically, the applications presented are profit testing, calculation of value of liabilities, liability adequacy test and estimation of company value (embedded value). The thesis is structured in three chapters. Firstly, life insurance companies and their products are introduced. Then the cash flows model and its components are described in detail. The third chapter presents each application one by one, firstly of their main principle and then demonstrates with a real example of endowment product. The thesis is a consolidated source of cash flows model’s application in life insurance.